A pH-responsive bi-MIL-88B MOF coated with folic acid-conjugated chitosan as a promising nanocarrier for targeted drug delivery of 5-Fluorouracil - Akbar, Muhammad Usman; Khattak, Saadullah; Khan, Malik Ihsanullah; Saddozai, Umair Ali Khan; Ali, Nemat; AlAsmari, Abdullah F.; Zaheer, Muhammad; Badar, Muhammad (Frontiers in Pharmacology, 2023)
Cancer has remained one of the leading causes of death worldwide, with a lack of effective treatment. The intrinsic shortcomings of conventional therapeutics regarding tumor specificity and non-specific toxicity prompt us to look for alternative therapeutics to mitigate these limitations. In this regard, we developed multifunctional bimetallic (FeCo) bi-MIL-88B-FC MOFs modified with folic acid—conjugated chitosan (FC) as drug delivery systems (DDS) for targeted delivery of 5-Fluorouracil (5-FU). The bi-MIL-88B nanocarriers were characterized through various techniques, including powder X-ray diffraction, scanning electron microscopy, energy-dispersive X-ray, thermogravimetric analysis, and Fourier transform infrared spectroscopy. Interestingly, 5-FU@bi-MIL-88B-FC showed slower release of 5-FU due to a gated effect phenomenon endowed by FC surface coating compared to un-modified 5-FU@bi-MIL-88B. The pH-responsive drug release was observed, with 58% of the loaded 5-FU released in cancer cells mimicking pH (5.2) compared to only 24.9% released under physiological pH (5.4). The in vitro cytotoxicity and cellular internalization experiments revealed the superiority of 5-FU@bi-MIL-88B-FC as a highly potent targeted DDS against folate receptor (FR) positive SW480 cancer cells. Moreover, due to the presence of Fe and Co in the structure, bi-MIL-88B exhibited peroxidase-like activity for chemodynamic therapy. Based on the results, 5-FU@bi-MIL-88B-FC could serve as promising candidate for smart DDS by sustained drug release and selective targeting.